Consumer Innovativeness and the Adoption Process - Manning, Kenneth C.; Bearden, William O.; Madden, Thomas J. (Journal of Consumer Psychology, 1995)
Two conceptualizations of innovativeness are operationalized and related to the new product adoption process. Multi‐item scales designed to measure consumer independent judgment making (i.e., the degree to which an individual makes innovation decisions independently of the communicated experience of others) and consumer novelty seeking (i.e., the desire to seek out new product information) are developed and tested on adult consumers. Tests of the hypothesized effects of these traits show that consumer novelty seeking is positively related to early stages of the adoption process (i.e., actualized novelty seeking and new product awareness), whereas consumer independent judgment making is only associated with later stages of the adoption process (i.e., new product trial). The implications of these findings and suggestions for future research are also discussed.